The potential and challenges of Ampang Jaya Municipal Council (MPAJ) towards achieving low carbon city (LCC) : community perspectives
The goal of reducing carbon emissions by 30% by 2030 in Ampang Jaya requires participation from local authorities and the community itself. Thus, this study has been done to evaluate the potential Ampang Jaya Municipal Council (MPAJ) to achieve low carbon city (LCC). The Ampang Jaya area was selected as the area of observation because of its high population density and its high potential to achieve LCC. The study was conducted qualitatively using an in-depth semi-structured interview method and the data obtained were analysed using thematic analysis. Seven themes emerged from the in-depth interviews which can be incorporated into three dimensions namely themes execution and planning, enforcement of policies and, ongoing works by MPAJ under the dimension of readiness of local authorities; themes cleaner and healthier environment and, LCC in Ampang Jaya under the dimension of achievable milestones; and the themes of community’s daily lifestyle changes and roles by local authorities under the dimension of responsibilities. In principle, this research concludes that MPAJ has a high potential to achieve LCC while being able to overcome the challenges they face to achieve this feat.